Menopausal status and type 2 diabetes: a nationwide epidemiological survey in Vietnam. (September 2016) - Nguyen, C.T.; Pham, N.M.; Nguyen, Q.V.; Nguyen, V.Q.; La, Q.N.; Lee, A.H.
Highlights: The average age at menopause among women in Vietnam was 49 years. There was a lack of significant association between menopause and type 2 diabetes. Age and body mass index were significantly associated with type 2 diabetes.